Design and development of semi automatic canting tool (Electrical) - Amir Asri, Mohd Al Kharid (2012)
In traditional canting processes, the wax has to be melted on a stove, then the molten wax will be poured into canting tool, and the canting tool will be used to make sketches on a cloth. The traditional method is complicated and required skills just for preparation of canting processes. Semi automatic canting tool is a tool that is equipped with a heating element to melt the wax directly inside the canting tool and will make the canting process easier especially to beginner. This research is done by two researchers and divided by two main tasks. The first task is research on the mechanical design and mechanism of the semi automatic canting tool. The second task is about the heating element and analysis on the wax and this research is focus o the second task. Research on the heating element is about the type of heating element, type of power source and the material for the heating element. For analysis on the wax, the scope is on the physical properties, melting point, and the flow of molten wax.